The relation between Total Quality Management & Human Resources Management-the importance of HRM in TQM - Karabulut, Figen (My University, 2000)
Organizasyonlar, hızla gerçekleşen yenilikleri yakalabilmek ve rekabet ortamında bir yer edinebilmek için profesyonel anlamda değişimi hedeflemiş ve başlangıç noktasını daha çok müşteri odaklılık olarak belirlemişlerdir. Hem iç, hem de dış müşteriyi önemseyen ve bu yönde odaklanan felsefesi ile Toplam Kalite Yönetimi (TKY) ve İnsan Kaynakları Yönetimi (İKY) değişimi ve daha çok müşteri odaklılığı benimseyen organizayonların uyguladığı yeni sistemlerdendir. TKY, ürün ve hizmete direkt ve pozitif etki sağlayan sürekli gelişim prosesini önemseyen ve dolayısı ile şirket performansına artı katkı ve değer sağlayan bir yönetim biçimidir. TKY'de asıl hedef müşteri memnuniyetidir ve performansı yüksek iş gücü TKY uygulamalarını olumlu yönde etkileyecektir. Dış müşterinin satınalma gücü ve ürüne olan bağlılığı, İç Müşterinin organizasyona olan bağlılığı ve ürüne olan olumlu katkısı sürekli gelişim prosesinin organizasyonda oluşumunu sağlar. Bununla birlikte, sistematik planlar, istatistiksel araçlar ve katı prosedürlerden oluşan TKY, organizasyonun başarısında tek başına yeterli olamayabilir. Bu türden bir yönetim biçimi, kuruluşdaki insan -çalışan- faktörünüde kapsamı içine almalıdır. Organizasyondaki her türlü sürecin başlangıcında ve evrelerinde insan faktörü mevcuttur. Ünvan, pozisyon, departman, eğitim, kültür açısında çalışanlar birbirlerinden farklılık göstermektedirler ve her bir bireyin ihtiyaçları karşılanarak tatmin seviyeleri yükseltilmelidir. İnsan faktörü, kuruluşlarda İnsan Kaynakları Yönetimi uygulamalarının gerekliliğini ortaya koymuştur. TKY ve İKY'nin aynı anda uygulamada olması, kuruluşa yepyeni bir kültürün adaptasyonunu sağlar. İnsan Kaynakları uygulamaları ile potensiyel iş gücünün yukarılara çekilmesi, kaliteli üretimi etkileyecektir. Üretimin kalitesi, yüksek kazanç sağlayacak ve bu bağlamda şirket performansıda yükselecektir. Hizmet performansını iyileştirme sorumluluğunun tüm çalışanlara yaygınlaştırılması, diğer bir deyişle çalışanın katılımı kalitenin oluşumunu sağlar. Teorik açıdan incelendiğinde TKY ve İKY arasındaki ilişki açıktır. Bu nedenle de ilgili uygulamaların ortak hedef ve planlar doğrultusunda oluşturulması gerekmektedir. İçinde bulunduğumuz rekabet ortamında, değişim şarttır. Fakat değişimin kuruluş içerisinde tüm çalışanlar tarafında algılanabilmesi, özümsenebilmesi ve adapte edilebilmesi mutlak başarı için önemli ve gözden kaçırılmaması gereken noktalardır. Dolayısı ile araştırmanın amacı TKY ve İKY'nin teorisini ve günümüzde bu yönetim biçimlerini uygulayan firma çalışanlarına uygulanan anket vasıtası ile pratikteki uygulamaları karşılaştırmak ve çalışanların TKY ve İKY hakkındaki bilgi, algılama ve tatmin düzeylerini saptayabilmektir. Araştırma sonuçlarına göre, fırsat eşitliği, eğitim ve geliştirme programları, iş ortamında çalışanlara da yetki ve sorumluluk veren etkili bir liderlik anlayışı, bireysel hedeflerin, şirket hedefleri ile uyum içerisinde olması ve TKY ve İKY'ni açıklayan detaylı eğitim programlarının kuruluşlardaki gereksinimi, üzerinde hassiyetle durulması gereken konuları oluşturmaktadır. İKY ve TKY, organizasyonların başarısında söz sahibi, sistematik, yeniliğe açık ve birbirlerinin varlığına ihtiyaç duyan iki yönetim biçimidir. İç müşteri mutluluğunu hedefleyen İKY, sürekli gelişim prosesi ile dış müşteriyi hedefleyen TKY için son derece önemli ve vazgeçilmez bir sistemi oluşturmaktadır. THESIS SUBJECT: THE RELATION BETWEEN TOTAL QUALITY MANAGEMENT AND HUMAN RESOURCES MANAGEMENT AND THE IMPORTANCE OF HRM IN TQM

Organisations have realised that there is an urgent need to change their business practices and become more customer-focused. They have to find and try different types of systems and put them into action in order to catch the rapid changes. Total Quality Management (TQM) and Human Resources Management (HRM) are two of these new systems- management styles- concerning 'the changes' and focusing 'the customer '. TQM is one of the most important management styles by adding value to an organisation in our competitive world and it is a top management philosophy that emphasises the continuous improvement of the processes, which result in goods or services. Its ultimate goal is customer satisfaction. High performing work force effects the implementation of TQM in positive way. Customer satisfaction, from the point of external customer's loyalty and purchasing power, and Internal Customer's Commitment to the organisation and outputs provides the continuous improvement in TQM. However, as the collection of systematic plans, statistical tools and rigid procedures, TQM may not be adequate by itself for the success of the organisation. It also requires the belief to human beings that start each process in the organisation and takes individually part in the phases. Employees are different from each other by title, position, background, department, unit, culture and the need of each individual should be satisfied. The factor of 'human' brings the necessity of the implementation of Human Resources Management (HRM) in organisations. TQM requires the understanding and commitment of all organisational members to succeed and HRM is one of the main factors to provide this condition. The implementation of TQM and HRM at the same time brings the new and more flexible culture to the organisation this fact constitutes the subject of this study. High quality organisational performance is the result of profitability and productivity and HR is the management system to develop the potential work force in the organisation through the internal customers. Employee participation make quality happen and it is a certain result that quality brings productivity together when everybody is charged with the responsibility of improving service performance. In our competitive world, organisations must change, but to assimilate and adopt the change are the important points for the success. The knowledge, satisfaction and observation level of TQM and HRM by employees is the critical data to see the application and adaptation level of TQM and HRM in the organisations. Theoretically there should be a close effectiveness between HRM and TQM. The application of HRM and TQM should be directed according to the common targets pointed out by both Human Resources and Total Quality Managers. The objective of the research is to compare the theoretical side, depending on the literature survey, with practical applications of TQM and HRM in today's organisations in detail by questioning the knowledge, satisfaction and observation level of TQM and HRM by employees. Treating employees as individuals, fairly and equitably, offering services and programs for their improvement, effective leadership activities by giving employees responsibility in the job process to take decisions and team work increase their job satisfaction and commitment to the organisation. One of the most important tasks of HRM is to get high performance from the organisation's employees. Top-management should be aware of the importance of employee's high performance and give their support to HRM. Analysis of harmony between individual objectives and organisation objectives should be handled carefully. Employees who have quality consciousness focus on complete customer satisfaction through a comprehensive program that ensures every job is done right at the first time. This consciousness can only be given with TQM, which supports the organisation success deeply. HRM and TQM are both the systematic approaches for the successful organisation and the implementing TQM needs the existence of HRM in the organisation. The point is to explain the importance of HRM for a successful TQM application and indicate the importance of human beings factor, which is also defined as employee or internal customer in this study, for the successful application of HRM and TQM in the organisations.
Keywords: Genel yönetim; İnsan Kaynakları Yönetimi-Toplam Kalite Yönetimi; İnsangücü Planlaması-Toplam Kalite Yönetimi; Personel yönetimi